The Application Of Macrame Rope Activity For Improving Fine Motor Skills of Children Aged 5-6 Years in Semesta Kindergarten School - Damayanti, Lingga Mulki; Diana (Universitas Negeri Semarang, 2025)
One aspect of development that must be well stimulated for early childhood is fine motor skills. Various kinds of activities can be carried out in Children Education to improve children's fine motor skills, for example with weaving activities. This study aims to determine the effect of macrame rope weaving activities in improving fine motor skills of children aged 5-6 years at Semesta Semarang Kindergarten. This study used a quantitative method with a one group pretest and post-test research design. The population and sample in this study were children aged 5-6 years at Semesta Semarang Kindergarten, totaling 40 children. Data collection was done through direct observation and question and answer with the teacher. The data that has been collected are processed by normality test, homogeneity test, paired sample T-test hypothesis test, and finally N-gain test using the help of SPSS V.26 data processing application. The average result of pretest data was 59.95 and the average post-test value was 109.6. Then the paired sample t-test hypothesis test was carried out with a significance result of 0.000 <0.05, then H0 was rejected and H1 was accepted, that means there was a significant difference in children's fine motor skills before and after treatment. Then through the N-gain test produced a value of 82.8414 or 82.8%, it can be concluded that through makrame rope weaving activities, it has a high effective effect on increasing children's fine motor skills.